Clues to the universe eaudiobook - Li, Christina (2021)
This stellar debut by APALA Award–winning author Christina Li about losing and finding family, forging unlikely friendships, and searching for answers to big questions will resonate with fans of Erin Entrada Kelly and Rebecca Stead. The only thing Rosalind Ling Geraghty loves more than watching NASA launches with her dad is building rockets with him. When he dies unexpectedly, all Ro has left of him is an unfinished model rocket they had been working on together. Benjamin Burns doesn't like science, but he can't get enough of Spacebound, a popular comic book series. When he finds a sketch that suggests that his dad created the comics, he's thrilled. Too bad his dad walked out years ago, and Benji has no way to contact him. Though Ro and Benji were only supposed to be science class partners, the pair become unlikely friends, and Ro even figures out a way to reunite Benji and his dad. But Benji hesitates, which infuriates Ro. Doesn't he realize how much Ro wishes she could be in his place? As the two face bullying, grief, and their own differences, Benji and Ro try to piece together clues to some of the biggest questions in the universe. A Washington Post KidsPost Summer Book Club selection * A Junior Library Guild Selection * A Bank Street Best Book of the Year